Effect of feed enzymes and functional immunostimulants supplementation on growth performance and overall health of postlarvae and juvenile Pacific white shrimp, Penaeus vannamei, fed soybean‐based diets - Niti Chuchird; Tirawat Rairat; Arunothai Keetanon; Daranee Seguin; Rutchanee Chotikachinda; Lukas Manomaitis; Chuchai Kanjanamayoon (Journal of the World Aquaculture Society, 2023)
Abstract Soybean meal (SBM) is widely used in shrimp feed agro‐industry as a fish meal (FM) replacement. However, high levels of SBM may compromise animal health as a result of nutrient imbalance. This study aimed to investigate the effects of feed enzyme combination (a mixture of 6‐phytase, serine protease, and endo‐1,3(4)‐β‐glucanase) and functional immunostimulant combination (a mixture of brewer's yeast, nucleotides, vitamin C, and vitamin E) in improving the overall health of Pacific white shrimp fed soybean‐based diet. Four diets were formulated with different amounts of SBM, FM, and poultry meal (PM): 0% SBM (with 25% FM and 12.6% PM), 30% SBM (with 12.5% FM and 5.7% PM), 30% SBM plus 0.045% feed enzymes, and 30% SBM plus 0.1% functional immunostimulants. The postlarvae were fed the test diets for 45 days. Then, the body weight, survival, FCR, Vibrio spp. count, and immune responses were analyzed. The resistance of shrimp to Vibrio parahaemolyticus infection was also evaluated. The results suggest that the diet with 30% SBM was deleterious to the shrimp's health. Feed enzymes and functional immunostimulant supplements improved overall performance, immune function, and resistance to V. parahaemolyticus infection of shrimp fed the diet containing 30% SBM compared with the 30% SBM diet without feed supplements.